The Performance of School Assignment Mechanisms in Practice - Monique de Haan; Pieter A. Gautier; Hessel Oosterbeek; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2015)
Theory points to a potential trade-off between two main school assignment mechanisms; Boston and Deferred Acceptance (DA). While DA is strategy-proof and gives a stable matching, Boston might outperform DA in terms of ex-ante efficiency. We quantify the (dis)advantages of the mechanisms by using information about actual choices under Boston complemented with survey data eliciting students' school preferences. We find that under Boston around 8% of the students apply to another school than their most-preferred school. We compare allocations resulting from Boston with DA with single tie-breaking (one central lottery; DA-STB) and multiple tie-breaking (separate lottery per school; DA-MTB). DA-STB places more students in their top-n schools, for any n, than Boston and results in higher average welfare. We find a trade-off between DA-STB and DA-MTB. DA-STB places more students in their single most-preferred school than DA-MTB, but fewer in their top-n, for n ≥ 2. Finally, students from disadvantaged backgrounds benefit most from a switch from Boston to any of the DA mechanisms.
Keywords: C83; D47; I20; 330; school choice; Boston mechanism; deferred acceptance mechanism; strategic behavior; ex-ante efficiency; ex-post efficiency